Does Online Salience Predict Charitable Giving? Evidence from SMS Text Donations - Carlo Perroni; Kimberley Ann Scharf; Oleksandr Talavera; Linh Vi (Center for Economic Studies and ifo Institute (CESifo), 2021)
We explore the link between online salience and charitable donations. Using a unique dataset on phone text donations that includes detailed information on the timing of cash gifts to charities, we link donations to time variation in online searches for words that appear in those charities' mission statements. The results suggest that an increase in the online salience of the activities pursued by different charities affects the number and volume of donations made to those charities and to charities that pursue different goals. We uncover evidence of positive “own-salience” effects and negative “cross-salience” effects on donations.
Keywords: H41; D12; D64; 330; charitable donations; online search; news shocks